Morphological diversity of benthic Nostocales (Cyanoprokaryota/Cyanobacteria) from the tropical rocky shores of Huatulco region, Oaxaca, México - González-Resendiz, Laura; León-Tejera, Hilda; Gold-Morgan, Michele (Phytotaxa, 2015)
The supratidal and intertidal zones are extreme biotopes. Recent surveys of the supratidal and intertidal fringe of the state of Oaxaca, Mexico, have shown that the cyanoprokaryotes are frequently the dominant forms and the heterocytous species form abundant and conspicuous epilithic growths. Five of the eight special morphotypes (Brasilonema sp., Myochrotes sp., Ophiothrix sp., Petalonema sp. and Calothrix sp.) from six localities described and discussed in this paper, are new reports for the tropical Mexican coast and the other three (Kyrtuthrix cf. maculans, Scytonematopsis cf. crustacea and Hassallia littoralis) extend their known distribution.